(untitled) (Biological Sciences - PJSIR, 2024)
Several species from the Brassica genus are very important agricultural crops cultivated in different parts of the world and also known to be heavy metals (HMs) accumulators. In our present research work, Brassica juncea L. was grown in soil spiked with different concentration levels (0.2 mm, 2 mm and 20 mm) of chromium (Cr) under natural environmental conditions. Plants were treated with Cr resistant bacterial strains (E.coli, Klebsiella, Staphylococcus and Salmonella). The visible symptoms after the exposure of Cr to B. juncea appeared in the form of a reduction in plant growth, leaf length, leaf width, leaf area and lower the plant biomass accumulation. Likewise, the reduction in photosynthetic pigments (chlorophyll and carotenoids) in leaves varied at different concentrations. The accumulation of lipid per- oxidation in leaves was determined as 2 thiobarbituric reactive metabolites, chiefly malondialdehyde. The results revealed that the inhibitory responses of both Cr on plant growth which were dependent on concentration and time. It was investigated by applying different HMs resistance bacterial strains to soil. The plant growth increased by decreasing the effect of Cr. In a nutshell, this study indicated that the utilization of bio-fertilizers (bacterial strains) for enhancing the plant’s growth and reducing Cr stress in soil which is beneficial in stress reading programs.